(untitled) (Modern Problems of Metallurgy, 2019)
The low specific power of the transformer in combination with the increased heat losses due to the geometrical factor and the unstable operation with long downtimes are predetermined by low technical and economic indicators of production, in comparison with the EAF of the "big" metallurgy. An urgent task is to search for low-cost methods to increase the energy efficiency of furnaces of this class by simulating the thermal work of the elements of the working space. Numerical simulation of heat transfer in the working space of foundry class AC EAF with a capacity of 3 tons has shown that with a duration of furnace downtime of 18–20 hours or more, replacing 40% of the walls lining and 16-20% of the roof lining by water cooled elements with a volumetric structure accumulating the skull, with using of “deep" bath with a reduced by 14–15% diameter of the radiating surface allows, at a given melting mass, to reach the energy consumption level of the furnace with a fully refractory lining and lower with a significant saving of refractories. Preloading scrap into the furnace in downtime increases energy efficiency, all other things being equal.